2000
DOI: 10.1136/gut.47.5.618
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of early gastric cancer: a non-concurrent, long term, follow up study

Abstract: Background-Controversy has arisen on the natural history of early gastric cancer (EGC). While some emphasise the eVectiveness of early detection in reducing mortality from gastric cancer, others insist that EGC is a pseudo-cancer. Aims/patients/methods-To elucidate the natural history of EGC, a nonconcurrent, long term, follow up study was conducted in 71 patients who were diagnosed endoscopically as having EGC, which was confirmed as cancer on biopsy, but in whom surgical resection was not conducted or delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
3
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(137 citation statements)
references
References 8 publications
4
125
3
5
Order By: Relevance
“…Several long-term follow-up clinical studies support the notion that human gastric carcinogenesis is a multistep and multifactorial process (Tsukuma et al, 1983(Tsukuma et al, , 2000Rugge et al, 2003). Progression of low-and high-grade non-invasive neoplastic lesions to invasive adenocarcinoma, and of early gastric lesions to advanced stages has been clinically documented (Tsukuma et al, 1983(Tsukuma et al, , 2000Rugge et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Several long-term follow-up clinical studies support the notion that human gastric carcinogenesis is a multistep and multifactorial process (Tsukuma et al, 1983(Tsukuma et al, , 2000Rugge et al, 2003). Progression of low-and high-grade non-invasive neoplastic lesions to invasive adenocarcinoma, and of early gastric lesions to advanced stages has been clinically documented (Tsukuma et al, 1983(Tsukuma et al, , 2000Rugge et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Progression of low-and high-grade non-invasive neoplastic lesions to invasive adenocarcinoma, and of early gastric lesions to advanced stages has been clinically documented (Tsukuma et al, 1983(Tsukuma et al, , 2000Rugge et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the recurrence is confined to the regional lymph nodes and detected early, with a small number of affected nodes, surgical resection can be an effective and curative treatment. When patients with EGC are left untreated, several studies have reported that approximately 25-64% of the cancers progress to the advanced stage and half of the patients die of gastric cancer progression within 5 years of diagnosis [23,24]. The disease course might be similar in cases of extragastric recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect the relatively long natural history of gastric adenoma and early gastric cancer. A follow-up study on the natural history of 56 early gastric cancers demonstrated that half of the lesions remained at an early stage of gastric cancer 44 months after diagnosis (9). Another study on gastric adenomas revealed that only 4 out of 27 lesions progressed to early gastric cancers during the median follow-up period of 66 months (10 (7).…”
mentioning
confidence: 99%